Modulation of early cortical processing during divided attention to non‐contiguous locations. (7th March 2014) - Frey, Hans‐Peter; Schmid, Anita M.; Murphy, Jeremy W.; Molholm, Sophie; Lalor, Edmund C.; Foxe, John J.
Abstract We often face the challenge of simultaneously attending to multiple non‐contiguous regions of space. There is ongoing debate as to how spatial attention is divided under these situations. Whereas, for several years, the predominant view was that humans could divide the attentional spotlight, several recent studies argue in favor of a unitary spotlight that rhythmically samples relevant locations. Here, this issue was addressed by the use of high‐density electrophysiology in concert with the multifocal m‐sequence technique to examine visual evoked responses to multiple simultaneous streams of stimulation. Concurrently, we assayed the topographic distribution of alpha‐band oscillatory mechanisms, a measure of attentional suppression. Participants performed a difficult detection task that required simultaneous attention to two stimuli in contiguous (undivided) or non‐contiguous parts of space. In the undivided condition, the classic pattern of attentional modulation was observed, with increased amplitude of the early visual evoked response and increased alpha amplitude ipsilateral to the attended hemifield. For the divided condition, early visual responses to attended stimuli were also enhanced, and the observed multifocal topographic distribution of alpha suppression was in line with the divided attention hypothesis. These results support the existence of divided attentional spotlights, providing evidence that the corresponding modulation occurs during initial sensory processing time‐frames in hierarchically early visual regions, and that suppressive mechanisms of visual attention selectively target distracter locations during divided spatial attention.